INDUSTRI KREATIF “TENUN MUNA” DAN PEMASARAN ONLINE (studi deskriptif dinamika pemasaran hasil tenun daerah Kabupaten Muna Sulawesi Tenggara) - Wa Ode Lusianai; La Tarifu; Ikrima Nurfikria; Aryuni Salpiana Jabar (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Weave is the identity and wealth inherent in a region. In Muna district, it is also known tohave high quality weave with diverse and interesting motifs. However the fundamental problem amongweavers is the limited media or means of promotion and sale of their weaving products. The lack ofknowledge and skills in utilizing the information technology; also the fear of weavers on motifs "theft"by other weavers are two major problems the Muna's weaving was unpublished. This research wasconducted to identify the marketing mode of Muna’s weaving and the use of IT-based communicationmedia in its marketing. Using a qualitative research model, research data was collected throughinterviews and observations and then analyzed using qualitative descriptive data analysis of Miles andHuberman's interactive models. The research findings indicated that the marketing mode of weavingwas carried out by weavers through collectors or gallery owners and also directly sold to the peoplewho come to the weave. In addition, weavers also labeled each weaving motif as intellectual propertyright, and then published it through their respective online media by filling out the account with thecontent profile type or weaving motifs produced, weaving activities, and woven drawings withcaptions or messages to illustrate the images. Serious steps are needed among the government,weavers and the public for the dissemination and education of use and the need for proposing anintellectual property right (haki) for each woven work motif produced so that there is no longer asense of fear of "theft" motifs.